Do You Track? A Look at the Difference Between Great Plains and Southeast Tornado Tracks - Isaac Abdullayev (UNC Test Journal, 2024)
Tornadoes in the southeastern United States and in the Great Plains have both similarities and differences. For instance, Great Plains tornadoes are typically spawned out of individual supercells, while many more southeastern tornadoes are a part of synoptically-driven disturbances such as quasi-linear convective systems. Wintertime tornadoes also occur more frequently in the Southeast than in the Great Plains. Another difference can be seen in the tracks of Southeast and Great Plains tornadoes. Therefore, this paper compares tornado tracks from the southeastern United States and the Great Plains after the implementation of the EF-scale. The comparison includes average tornado length and width for each EF rating, as well as track length and width in the spring and winter seasons. Results indicate that weaker tornadoes (EF-0 and EF-1) are relatively similar across both regions. However, as the tornado strength increases, the distances traveled and base widths across both regions are no longer as similar.